2012
DOI: 10.1371/journal.pone.0036222
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Resting-State Network Connectivity in Tinnitus: A Functional MRI Study

Abstract: The underlying functional neuroanatomy of tinnitus remains poorly understood. Few studies have focused on functional cerebral connectivity changes in tinnitus patients. The aim of this study was to test if functional MRI “resting-state” connectivity patterns in auditory network differ between tinnitus patients and normal controls. Thirteen chronic tinnitus subjects and fifteen age-matched healthy controls were studied on a 3 tesla MRI. Connectivity was investigated using independent component analysis and an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
168
2
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 206 publications
(189 citation statements)
references
References 53 publications
17
168
2
2
Order By: Relevance
“…For the authors, the reciprocal negative correlations in connectivity between these networks might be maladaptive or reflect adaptations to reduce phantom noise salience and conflict with attention to nonauditory tasks. In a recent fMRI study, we compared the restingstate auditory activity of thirteen tinnitus patients and fifteen controls (Maudoux et al, 2012). Our results suggested that the tinnitus percept is not only linked to activity in sensory auditory areas but is also associated to connectivity changes in limbic/ parahippocampal areas, basal ganglia/nucleus accumbens, higher-order prefrontal/parietal associative networks, infratentorial brainstem/cerebellar and sensory-motor/visual-motor systems.…”
Section: Introductionmentioning
confidence: 88%
“…For the authors, the reciprocal negative correlations in connectivity between these networks might be maladaptive or reflect adaptations to reduce phantom noise salience and conflict with attention to nonauditory tasks. In a recent fMRI study, we compared the restingstate auditory activity of thirteen tinnitus patients and fifteen controls (Maudoux et al, 2012). Our results suggested that the tinnitus percept is not only linked to activity in sensory auditory areas but is also associated to connectivity changes in limbic/ parahippocampal areas, basal ganglia/nucleus accumbens, higher-order prefrontal/parietal associative networks, infratentorial brainstem/cerebellar and sensory-motor/visual-motor systems.…”
Section: Introductionmentioning
confidence: 88%
“…All episodic artifacts were removed from the stream of the EEG. Average Fourier cross-spectral matrices were computed for bands delta (2-3.5 Hz), theta (4-7.5 Hz), alpha (8-12 Hz), beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and gamma (30.5-45 Hz).…”
Section: Connectivity Changes Between Cases 1 Andmentioning
confidence: 99%
“…11 Apart from abnormal activity, pathological functional connectivity is also associated with the presence of tinnitus as demonstrated by electroencephalography (EEG), 57 magnetoencephalography (MEG), 38,39 and functional MRI (fMRI). 26,27 Thus, it has been proposed that the phenomenologically unified percept of tinnitus can be considered an emergent property of multiple, parallel, dynamically changing, and partially overlapping subnetworks, each with a specific spontaneous oscillatory pattern and functional connectivity signature. 17 Functional imaging studies using source-localized EEG and MEG have shown that tinnitus distress is related to a network involving the anterior cingulate cortex (ACC), anterior insula, and parahippocampal area, 6,22,56 whereas the auditory cortex is involved in the perceived tinnitus intensity.…”
mentioning
confidence: 99%
“…Further support for this model comes from resting-state fMRI-studies. In a mixed sample of bothered and non-bothered tinnitus patients according to the Tinnitus Questionnaire (TQ) [30], tinnitus patients showed higher functional connectivity within an auditory resting-state network in comparison to healthy controls bilaterally in the parahippocampal gyrus, the inferior frontal gyrus, right prefrontal cortex, right inferior parietal lobe and postcentral gyrus [31]. A resting-state fMRI-analysis on bothered tinnitus patients showed greater functional connectivity as compared to HC between the right anterior insula and left inferior frontal gyrus which correlated positively with activity in the auditory cortex [32].…”
Section: Introductionmentioning
confidence: 99%